2022
DOI: 10.1155/2022/9925267
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Mediterranean Diet and Its Association with Metabolic Health Status in Overweight and Obese Adolescents

Abstract: Background. Obesity is becoming more prevalent around the world and greatly contributes to chronic disease progression. Previous studies have investigated individual food groups in relation to metabolic health status of adolescents, mainly in Western countries. Limited data are available on the association between dietary patterns and metabolic health in Middle East nations, where childhood overweight/obesity is increasing drastically. Therefore, we investigated the relationship between the Mediterranean diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Interestingly, they found that in post-menopausal state but not in premenopausal, higher adherence to MD was associated with a lower risk of MUO phenotype [ 33 ]. Also in adolescence, this association has been confirmed [ 34 ]. Indeed, a cross-sectional study was carried out in 203 adolescents with overweight/obesity.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, they found that in post-menopausal state but not in premenopausal, higher adherence to MD was associated with a lower risk of MUO phenotype [ 33 ]. Also in adolescence, this association has been confirmed [ 34 ]. Indeed, a cross-sectional study was carried out in 203 adolescents with overweight/obesity.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, a cross-sectional study was carried out in 203 adolescents with overweight/obesity. A validated food frequency questionnaire was administered in order to investigate dietary intakes, and an inverse association between MD and odds of MUO phenotype was found among Iranian adolescents [ 34 ]. The same results were found in the HELENA study, which was carried out in 137 adolescents with obesity or overweight in order to investigate the association of MUO phenotype with MD [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MD, rich in nutrients and phytochemicals known for their anti-inflammatory role, including vitamins C and E, epigallocatechin gallate, lycopene, and polyphenols, could modulate inflammatory components such as NF-KB, mitogen-activated protein kinases, and IL-1β signaling [55]. Lastly, the high fiber content of the MD could have an antiinflammatory role due to the major production of SCFAs by gut bacteria, which could improve glucose and lipid metabolism in many tissues [64,65]. The changes in the gut microbiota are strictly related to the type of fatty acids ingested: the altered n-6/n-3 PUFAs ratio was found to promote the development of Enterobacteriaceae and Clostridia spp., leading to a pro-inflammatory environment that could be attenuated by the introduction of n-3 PUFAs [66,67].…”
Section: Diet-related Diseases Obesity and Metabolic Syndromementioning
confidence: 99%
“…For diseases re ing a specific diet, there are few and heterogeneous studies available for children. F research should focus more on the specific nutritional changes required to enable di control, both in terms of dietary patterns and specific nutrients' intake, and how these influence the risk of occurrence of other diseases or the composition of the gut micro Eight studies on both children and adolescents [43,47,48,50,57,58,64,65] Nutrition is an environmental factor that ences inflammatory pathways. Several av ble studies evaluate not only individual n ents or foods, but investigate nutrition c plexity through dietary pattern analys…”
Section: Depletion Of Scfas-producing Bacteriamentioning
confidence: 99%
“…Among dietary patterns, over the last decades great attention has been paid to the Mediterranean diet (MedDiet), as a balanced nutritional pattern associated with increased metabolic health status in children and adolescents [ 120 ]. MedDiet is characterized by the high intake of vegetables, fruits, legumes, and cereals (mainly in unprocessed forms); the low intake of meat and meat products and low to moderate intake of dairy products; the moderate to high intake of fish; and the high intake of unsaturated added lipids, particularly in the form of olive oil [ 121 ].…”
Section: Nutritional Strategies For Modulation Of Insulin Resistancementioning
confidence: 99%